Emergency remote teaching and learning vs face-to-face: When are students more likely to fall behind? - Knoetze, A.; du Toit, Y. (South African Journal of Higher Education, 2022)
The COVID-19 global pandemic brought about a shift from traditional face-to-face teaching and learning to emergency remote teaching and learning (ERT) in higher education institutions across the world. Prior studies have explored both instructor and student perceptions of ERT and identified self-regulated learning (SRL) as a major challenge. The question remains whether perceptions translate to student behaviour and if so, it will be important to address these self-regulation challenges as poor SRL has been linked to weaker academic achievement. This study investigated whether students exhibit inferior SRL strategies in ERT by falling further behind, as compared to a face-to-face setting. In order to measure how far behind students are, student access log-data from four undergraduate modules offered at Stellenbosch University in the 2019 (face-to-face setting) and 2020 (ERT setting) academic years were used. An analysis of variances model tested whether there was a difference in the number of days that students were behind for the two modes of teaching and learning. The results indicate that students are indeed more likely to fall behind during ERT as compared to face-to-face teaching and learning, thus exhibiting inferior SRL. This was statistically significant and pervasive across the different modules and time period investigated. These results will be of interest to higher education institutions as the onslaught of the pandemic has not only highlighted the need for improved ERT readiness, but it has also brought to the fore the need for a more digitally integrated offering as standard practice. Since it is unlikely that higher education institutions will return to a model identical to the pre-COVID-19 offering, this study contributes to finding the focus areas that will need to be addressed in a future hybrid model of teaching and learning.